2012
DOI: 10.1002/adfm.201201242
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Fibers as a Solid‐State Real‐Time Zinc Ion Sensor with High Sensitivity and Cell Medium Compatibility

Abstract: Abstractmeso‐2,6‐Dichlorophenyltripyrrinone (TPN‐Cl2), a probe molecule for zinc II ions, is dispersed in a polymer host. The red fluorescence peak at 620 nm appears when the molecule forms a complex with zinc at its center. TPN‐Cl2 has a high selectivity for zinc II and tolerates many common metal ions present in the human body. The probe molecules are blended with a hydrogel polymer, poly(2‐hydroxyethyl methacrylate) (poly HEMA), with 30 wt% dimethylformamide (DMF). The fiber structure with 1 μm diameter is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The photoluminescence spectra of the TPN-Cl 2 -doped poly HEMA nanofibrous film showed that the introduction of Zn 2+ in the concentration range of 0-10 −6 M demonstrated that the emission peak at 620 nM was responsible for Zn 2+ , which becomes a shoulder, remains responsive, and is attributed to the formation of a complex between Zn and TPN-Cl 2 (see Figure 22). The sensing performance of the fibrous film has been noted with a detection limit of 10 −6 M, which is higher than the planar film [130].…”
Section: Detection Of Zinc Ionsmentioning
confidence: 95%
See 2 more Smart Citations
“…The photoluminescence spectra of the TPN-Cl 2 -doped poly HEMA nanofibrous film showed that the introduction of Zn 2+ in the concentration range of 0-10 −6 M demonstrated that the emission peak at 620 nM was responsible for Zn 2+ , which becomes a shoulder, remains responsive, and is attributed to the formation of a complex between Zn and TPN-Cl 2 (see Figure 22). The sensing performance of the fibrous film has been noted with a detection limit of 10 −6 M, which is higher than the planar film [130].…”
Section: Detection Of Zinc Ionsmentioning
confidence: 95%
“…Therefore, the colorimetric determination of Zn 2+ has also been attracted accountable interest; correspondingly, very few efforts have been directed toward the electrospun nanofiber-based colorimetric detection of Zn 2+ . For example, meso-2,6-dichlorophenyltripyrrinone (TPN-Cl 2 ), a red fluorescent probe sensitive to Zn 2+ has been doped into hydrogel polymer poly(2-hydroxyethyl methacrylate) (poly HEMA) and electrospun to obtain nanofibrous film that was further used for the detection of Zn 2+ in water [130]. A planar film has been also fabricated using similar composition for the purpose of comparing their sensing efficiency.…”
Section: Detection Of Zinc Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various solid‐state sensing materials, flexible fluorescent hydrogel films are attracting increasing attention in recent years . This is because hydrogels are hydrophilic, water swellable polymer networks that can allow efficient diffusion of water‐soluble pollutants into the hydrogel matrix .…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is generally measured by Stern–Volmer plots and visualized by fluorescent microscopy. Many optical nanofibrous sensors for electron‐deficient compounds such as explosives and heavy metal ions have been designed based on this technique by either doping fluorescent compounds into the electrospinning solution, chemically modifying nanofibers, or “decorating” the surface of the nanofibers . Very often, these changes in fluorescence intensity can be seen with the naked eye or with the help of relatively simple equipment such as light emitting diode (LED) light sources, charge‐coulpled device (CCD) cameras or compact inexpensive spectrometers .…”
Section: Introductionmentioning
confidence: 99%